Problem-based learning worksheet integrating Islamic values to facilitate elementary students’ critical thinking in natural and social sciences - Agustang, Agustang; Wati, Unik Ambar; Kartika, Lia Nur (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
Twenty-first-century competency frameworks emphasize critical reasoning as a core skill, while integrating Islamic values into education is considered important for providing an ethical foundation in students’ decision-making. However, there are still limited digital worksheets that combine Problem-Based Learning (PBL) with Islamic values in elementary natural and social sciences. This study developed and evaluated the feasibility of a PBL-based digital worksheet integrating Islamic values for Grade 5 natural and social sciences learning. The research and development design followed the ADDIE model: analysis, design, development, implementation, and evaluation. The product (a digital presentation, a student worksheet guide, and interactive worksheets) was validated by experts and trialed with 19 Grade 5 students and 1 teacher in Yogyakarta. Instruments included expert validation questionnaires and user response questionnaires (5-point Likert scale); data were analyzed by calculating percentage scores and qualitatively assessing comments and observations. Expert validation indicated high feasibility (material expert 100%; media expert 84%). In a limited classroom trial, the worksheet’s practicality reached 76% (teacher) and 65.47% (students). Qualitative feedback identified technical constraints (e.g., connectivity issues), user behaviors (e.g., skipping tutorials, off-task web browsing), and the need to improve content clarity and simplify the presentation of Islamic values. Overall, the PBL worksheet integrating Islamic values was found to be valid and practical, but it requires technical refinements, enhanced digital scaffolding, and more concrete formulation of values to strengthen connections between environmental learning and Islamic principles. Practical implications include developing an offline or lighter version of the media, making tutorials non-skippable, and strengthening digital classroom management. Further research with a quasi-experimental design and a broader sample is recommended to test the worksheet’s effectiveness in improving students’ critical thinking.